Roger Ward Crosskey—The Life and Contributions of an Entomologist par Excellence (1930–2017) - Adler, Peter H. (Zootaxa, 2018)
The life of Roger Ward Crosskey stands as a paragon of scholarly dedication to the profession of entomology. His early interests in natural history prepared him for a diverse entomological career of about 65 years. He began as a medical entomologist working on the onchocerciasis problem with the Colonial Service in Northern Nigeria, and officially transitioned to dipterology, first studying the Tachinidae as a taxonomist with the Commonwealth Institute of Entomology, and later the Simuliidae as a Senior Principal Scientific Officer (Merit) with The Natural History Museum in London. His contributions to the fight against onchocerciasis (river blindness) and to the study of Diptera, particularly the Simuliidae, are an enduring legacy. An indexed chronological listing of his 247 publications is provided, in addition to lists of the taxa that he named and the taxa named in his honor.